PEMAHAMAN ORANG TUA TENTANG KEMATIAN ORANG PERCAYA BERDASARKAN 2 KORINTUS 5:1–10 - Ruata, Jayson (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Death is something that cannot be avoided by all living creatures and even humans. The meaning of the word "dead" in the Big Indonesian Dictionary is "has lost its life, is not alive anymore". In the sense that death is the end of life, the absence of life in biological organisms. All living things will eventually die, either due to natural causes such as illness or due to unnatural causes such as accidents. Thus death will be experienced by every person whether evil or good, poor or rich, believers or non-believers. The focus in this study is on parents' understanding at G.B Calvary Mogoyunggung about the death of believers based on 2 Corinthians 5: 1-10. The writing of this scientific work aims to find out the extent of the understanding of parents at G.B Calvary Mogoyunggung about the death of believers based on 2 Corinthians 5: 1-10. First, in theory the authors obtain and provide various data and information that can help the whole community, especially parents, in understanding and teaching the correct understanding of the death of believers based on 2 Corinthians 5: 1-10. Second, practically this research can provide a true understanding based on the Bible for all readers more specifically parents in their ministry and duty as parents to have a correct understanding of the death of believers in Mogoyunggung Village based on 2 Corinthians 5: 1-10. The research method is a qualitative method, which will be carried out at the Density of the Calvary Baptist Church in Mogoyunggung village, Dumoga Timur District, Bolaang Mongondow district. In the research effort the researcher asked for permission to introduce researchers from the Indonesian Institute of Theology (STTI) Manado to conduct research, and after obtaining permission from the Shepherd of the Calvary Congregation, the researcher will conduct research on parents related to the researcher's problem, namely the extent of parental understanding in The church is about human death. From the discussion above it turns out that there are still many parents who do not understand and some even do not understand the meaning of the death of believers based on Bible truth to be learned, to the church, taught to the next generation and for the growth of the faith of each person especially specifically to people in the Mogoyunggung Calvary Baptist Church. Parents need to understand life as a Christian believer to see death based on Bible truth because that will help parents understand, teach and interpret death for believers so that parents understand correctly how to live, believe and be with God even if they face and experience death. In addition, in the interview process there are some parents in giving their answers doubtful even some are not appropriate that they provide answers that are different from questions outside the researcher's questions. Because of all these problems, problems arise because parents do not understand the death of believers according to II Corinthians 5: 1-10. Mogoyunggung Village is a village located in Bolaang Mongondow Regency. Even so, this village has a population that is mostly people who have a very strong Minahasa culture. In this case Calvary Mogoyunggung Baptist Church congregation has a Minahasa cultural background. It is important to note that 20 informants are loyal parents in the ministry, some are ministers in the local church, some have good education and some do not, some have a good economy and some are mediocre. However, there is one of the informants who has the right understanding and answers according to what the researcher has studied is parents who have long been Christians, ordinary people who do not have a good education and sufficient economy, are not very influential in service or society but faithful in service.